Exploration Study of Knowledge Towards Hurricane Disasters of Elementary School Students in Lubuklinggau City - Susmini; Bambang Soewito; Septiyanti; Almaini; Sapondra Wijaya; Wahyu Dwi Ari Wibowo (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This study aims to determine the knowledge of hurricane disasters among elementary school students in Lubuklinggau City. Children from an early age must be given a proper understanding of the forms of disasters that may hit their area and how to deal with disasters when they come suddenly. Children's vulnerability to disasters is triggered by limited understanding of the risks around them, which results in a lack of preparedness in dealing with disasters. Lubuklinggau City is one of the cities prone to hurricane disasters. This study uses a quantitative approach with a survey method. The survey was conducted to determine the description of the condition of students' knowledge about hurricane disasters and how to respond to them. Furthermore, a descriptive analysis was carried out. The data needed in this study are primary data obtained from distributing questionnaires to 6th grade elementary school students in Lubuklinggau City whose homes were affected by the hurricane disaster. The research findings show that students' knowledge about hurricane disasters is still at a low level.